2020
DOI: 10.3390/ijerph17082804
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Health-Related Quality of Life and Physical Activity in Children with Hyperactivity

Abstract: The main purpose of this paper was to evaluate the relationship between health-related quality of life (HRQoL) and the frequency of physical activity in Spanish children aged 8 to 14 years with attention deficit hyperactivity disorder (ADHD). Sample selection was performed using the data obtained from the children’s questionnaire of the National Health Survey of Spain 2017 that is carried out with the children’s parents, and that had an initial size of 6106 participants. After the application of the inclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 65 publications
1
18
1
1
Order By: Relevance
“…It seems that the intensity and frequency of PA are two important factors in order to produce a positive effect on mental health. Moreover, other studies have reported that a higher level of PA is associated with better mental health [ 1 , 3 , 8 , 24 , 25 , 46 , 47 , 48 ]. For example, children who were physically active 1–3 or ≥4 times per week had a lower rate of internalizing and externalizing disorders in comparison to those who were never active [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It seems that the intensity and frequency of PA are two important factors in order to produce a positive effect on mental health. Moreover, other studies have reported that a higher level of PA is associated with better mental health [ 1 , 3 , 8 , 24 , 25 , 46 , 47 , 48 ]. For example, children who were physically active 1–3 or ≥4 times per week had a lower rate of internalizing and externalizing disorders in comparison to those who were never active [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In another study it has been reported that the more frequent and intense exercise was associated with better self-regulation, emotional ability, and decreased hyperactivity and impulsivity in children [ 8 ]. Gallego-Méndez et al reported that as the frequency of PA increased, ADHD children showed better scores in health-related quality of life [ 3 ]. In a systematic review of exercise intervention in children and adolescents with ADHD, it was demonstrated that at least parents or teachers reported considerable positive effects of exercise on ADHD in studies evaluating the long-term effects of exercise [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, evaluation that focuses on the relationships between physical activity and health-related quality of life is an important focus of research in this field. On the other hand, there is little research aimed at exploring parents’ knowledge and perceptions of their children’s physical activity, their ideas about its importance and impact on the way they experience diverse dimensions of a stressful life ( Gallego-Méndez et al, 2020 ; Spinelli et al, 2020 ; Yarımkaya and Esentürk, 2020 ) particularly during the Coronavirus outbreak. Exploring these issues, including the different perspectives of persons involved in families’ life ( Izquierdo-Sotorrío et al, 2016 ), could help provide recommendations and support programs for parents to guide their children’s physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…The Spanish National Health Survey is a series of studies that have been the main source of information on the perceived health of the population living in Spain. Gallego-Méndez et al [37] assessed the relationship between HRQOL using the National Health Survey of Spain (Encuesta Nacional de Salud de España 2017 -ENSE 2017) questionnaire and the frequency of physical activity in Spanish children aged 8-14 years with attention deficit hyperactivity disorder (ADHD). They showed significant differences between different levels of physical activity frequency, as well end contained the following dimensions: mental well-being, physical health, social relations and the environment.…”
Section: Ijomeh 2021;34(3)mentioning
confidence: 99%